2015
DOI: 10.1186/s13717-015-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and modeling of urban sprawl through remote sensing and GIS in Kuala Lumpur, Malaysia

Abstract: Introduction: Kuala Lumpur is currently experiencing a large-scale urban transformation. This study explores a multi-buffer ring method to investigate the spatial and temporal dynamics of urban growth in the Kuala Lumpur metropolitan area by using Geographical Information Systems (GIS) and remote sensing imageries from1989 to 2014. Methods: The first Landsat images from 1989, 2001, and 2014 were classified with maximum likelihood classification to produce land cover maps and identify four types of land cover: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 32 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…Several studies have analysed urban sprawl at regional, local and temporal scales (Boori et al, 2015;Griffiths et al, 2010). The urbanization pattern of the greater Asmara area in Eritrea was studied using satellite remote sensing data of Landsat.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analysed urban sprawl at regional, local and temporal scales (Boori et al, 2015;Griffiths et al, 2010). The urbanization pattern of the greater Asmara area in Eritrea was studied using satellite remote sensing data of Landsat.…”
Section: Introductionmentioning
confidence: 99%
“…It will allow 3.3 million job opportunity and projecting up to USD444 billion in investments by next year. The built-up area from the city centre to 50 km outward the city is decreased because of the high intensity and floor space in the city centre (Boori et al, 2015b). The influence of planning permission in the conversion of land and change of building use allowed most of the developers and owner to change their land or building into a profitable asset.…”
Section: Observation and Mapping (Qualitative Method)mentioning
confidence: 99%
“…The built-up area from the city centre to 50 km (Boori, Netzband, Choudhary, & Voženílek, 2015b) outward the city is decreased in 2014 because of the high intensity and floor space in the city centre while in 2015 it increased to 2573.10 acres (Noor, Rosni, Hashim, & Abdullah, 2018) because of the land use change in Strategic Planning Zone (SPZ) which resulted from the increased and decreased of development were involved many main category such as residential, commercial, institution and public facilities. From 1990 to 2010 showed that changes in green spaces in Kuala Lumpur because of the land use sprawl pattern and the built-up areas increased (Noor, Abdullah, & Manzahani, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.15405/epms.2019.12.59 Corresponding Author: Izuandi Yin Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2421-826X 598 Kuala Lumpur city density is increased which urban expansion rapidly growth toward east side of the city showing the fast and slow stage of growth (Boori, Netzband, Voženílek, & Choudhary, 2015a). The builtup area from the city centre to 50 km outward the city is decreased in 2014 because of the high intensity and floor space in the city centre (Boori, Netzband, Voženílek, & Choudhary, 2015b). The purposes of urban growth are to understand how cities grow (economics, demographics, and politics) (Farrell, 2017).…”
Section: Problem Statementmentioning
confidence: 99%